Practical Handbook of Endoscopic Ultrasonography - Akahoshi, Kazuya; Bapaye, Amol.; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
Endoscopic ultrasonography (EUS) has evolved from an obscure method of investigation in the 1980s to a distinct endoscopy subspecialty with interventional and therapeutic capabilities. The art of interpreting EUS images is a skill every endoscopist needs to master. This book helps to meet that need as it is concise, simple to read, and amply illustrated, and describes the technique in a step-by-step manner. Many high-resolution EUS images of diseases are included, and literature reviews are kept short and concise while separate discussions and illustrations are devoted to radial and linear techniques. The book can be used as a reference handbook in the endoscopy room, yet contains all of the relevant information required to perform EUS, interpret images, and reach a diagnosis. Important pathological conditions are thoroughly discussed using representative EUS images, pointing out salient differentiating features, and relevant literature reviews are included. The section on interventional EUS deals with advanced interventional or therapeutic procedures, and potential complications and methods to avoid them are discussed. For the novice, the book is designed to teach EUS using a step-by-step approach, and for the seasoned endosonographer it is a practical reference tool for use while performing EUS and may also serve in the differentiation of various pathologies.
Keywords: Medicine; Radiology, Medical; Diagnosis, Ultrasonic; Gastroenterology; Medicine & Public Health; Gastroenterology; Ultrasound; Imaging / Radiology